The Implementation of the Principle of Accountability in State Budget Management According to State Administrative Law - Rahmaningsih, Aziza Aziz; Gandeva Bayu Satrya (Istinbath : Jurnal Hukum, 2025)
The management of state finances based on legal principles will be good so that good governance can be realized in the administration of the state, the management of state finances needs to be carried out professionally, openly, and responsibly in accordance with the basic rules set out in the Constitution. The principle of accountability in the AAUPB strengthens for the organizers or management of state finances to be more responsible in accordance with the provisions of the applicable laws and regulations. Thus, the introduction of the result-oriented accountability principle or performance accountability in general principles, changes to the budget classification and the mechanism for determining the Work Plan and Budget (RKA) in the articles of Law No. 17 of 2003 concerning State Finance, because it is in accordance with the Principles of Accountability of Good governance related to good governance, which in a narrow sense, the implementation of good governance is related to the implementation of state administration. So that administrative law has a relationship between state finances and regional finances which is the result of government administration policies as part of managing the administrative system.